2013
DOI: 10.1364/oe.21.00a221
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon assisted Cu_xO photocatalyst for pure water splitting

Abstract: In this paper, Cu(x)O photocatalyst on plasmonic nanoporous Au film is proposed to enhancing the H(2) evolution rate of pure water splitting. The nanoporous Au film can simultaneously provide surface-enhanced absorption and built-in potential. The reflection spectrum shows that the surface plasmon (SP) assisted absorption wavelength of the Cu(x)O on the nanoporous Au film can be modified by changing the annealing temperature. It is found that the enhancement of the H(2) evolution rate highly depends on the SP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Domen and co-workers reported the photocatalytic overall decomposition of water into H2 and O2 on Cu2O particles of 300-500 nm size upon irradiation with visible light in the absence of any sacrificial electron donor at rates of approximately 2 µmol/g•h without observing decrease in the H2 evolution for more than 1900 h [22]. The photocatalytic activity of Cu2O to promote the overall water splitting has been later confirmed other research groups [23][24][25] and supported by first-principles calculations that show that the conduction and valence bands of most stable facets of Cu2O should have enough energy to promote overall water splitting and CO2 reduction [26]. In the area of catalysis by MNPs, theoretical as well as scattered experimental data have shown that different crystallographic planes may exhibit different specific activity [27,28].…”
Section: Introductionmentioning
confidence: 59%
“…Domen and co-workers reported the photocatalytic overall decomposition of water into H2 and O2 on Cu2O particles of 300-500 nm size upon irradiation with visible light in the absence of any sacrificial electron donor at rates of approximately 2 µmol/g•h without observing decrease in the H2 evolution for more than 1900 h [22]. The photocatalytic activity of Cu2O to promote the overall water splitting has been later confirmed other research groups [23][24][25] and supported by first-principles calculations that show that the conduction and valence bands of most stable facets of Cu2O should have enough energy to promote overall water splitting and CO2 reduction [26]. In the area of catalysis by MNPs, theoretical as well as scattered experimental data have shown that different crystallographic planes may exhibit different specific activity [27,28].…”
Section: Introductionmentioning
confidence: 59%
“…These results indicate that water molecules served as the electron donor in the plasmonic photoelectric conversion system and that a nearly stoichiometric evolution of O 2 and H 2 O 2 was achieved as a result of the oxidation of a water molecule with four or two photogenerated holes, respectively. Although numerous studies have achieved water oxidation or water splitting using the irradiation of visible light below wavelengths of 700 nm, 31,[53][54][55][56][57] this study is the first to achieve the stoichiometric evolution of O 2 from water molecules with the irradiation of near-infrared light at a wavelength of 1000 nm (1.24 eV). This result means that water oxidation via a four-electron transfer was accomplished by using a plasmonic photoelectric conversion system.…”
Section: Determining the Electron Source In The Plasmonic Photoelectrmentioning
confidence: 98%
“…[58] Later, aC u x Op hotocatalyst on plasmonic Au film with porouss tructure wasd eveloped by Wang et al to enhance the plasmonic water splitting. [59] Such ap lasmonic porous film can provide both enhanced light absorption and built-in potential. The reflections pectra also show that the absorption regiono ft he sample is tunable with different annealingt emperatures.…”
Section: Au-nontio 2 Photocatalystsmentioning
confidence: 99%
“…[58] The results also indicate that the optimal distance between CdS and Au NPs depends on the size of the Au NPs. [59] Such ap lasmonic porous film can provide both enhanced light absorption and built-in potential. [58] Later, aC u x Op hotocatalyst on plasmonic Au film with porouss tructure wasd eveloped by Wang et al to enhance the plasmonic water splitting.…”
Section: Au-nontio 2 Photocatalystsmentioning
confidence: 99%